Metode optimasi pada interkoneksi sistem suplai uap untuk kehandalan dan ekonomi pada sea water desalination - Angga Ridwan Pratama; Muhammad Agus Sahbana; Nova Risdiyanto Ismail (Universitas Muhammadiyah Metro, 2019)
Sea water desalination or desalination plant is an equipment that functions to change sea water into fresh water. Its reliability in supply water is important especially as raw material for the electricity generation process. Start-stop gas turbine operating mode as well as routine maintenance schedules or sudden damage in one of the desalination plant s cause a reduction in steam supply readiness. This research purposed to maintain the availability of supply steam desalination plant by using a method design interconnection line which is analyzed in terms of pressure drop and flow in theoretical calculations. This research resulted is design the interconnection line supply steam of the desalination plant by removing and modifying the position of the check valve dividing between desalination plant 1, 2 and 3. The analysis of the supply steam interconnection design in terms of pressure and flow desalination plant is still in accordance with the reference manual book. The operational cost of the desalination plant is more economical using supply steam from Block 1 Low-Pressure Auxiliary with a profit of 154.01% or 82,318,148 rupiahs per day. Keywords: Sea water desalination, interconnection line, pressure drop, flow, operational cost.